(untitled) (Biological Sciences - PJSIR, 1999)
Four varieties of guava (Psidium guajavay plants were treated against wilting. Integrated cultural practices and chemical measures for control of wilting were comparatively evaluated. Manuring with N, P, K and ZnS04, pruning of willed twigs, bandaging wounds with Ridomil paste and drenching of rhizosphere soils with nematicide were found to be the best among the treatments given. Continuous treatments at 15days interval helped in survival of the plants, which shot new leaves and shoots after 8-9 months. Deshipeyara were well protected with these treatments than vars. viz. Kazipeyara, Sarupkaui and Mukundhupuri. Integrated method of control arrested the wilting of young guava plants: